Bringing bioactive peptides into drug discovery: Challenges and opportunities for medicinal plants - Thakur S.; Punia A.; Satyakam; Acharya V.; Kumar B.; Prasad A.; Yadav S.K.; Kumar R. (My University, 2025)
The pervasiveness of lifestyle diseases is gradually increasing at an alarming rate worldwide. Physicians are prescribing many drug interventions to patients; however, the majority of them are found to have undesirable side effects. Thus, identifying natural alternatives is the principal goal of the pharma industry. Medicinal plants are the depository of diverse natural peptide products and peptides in the genome and awaiting their discovery. This review focuses on the techniques wet-lab and in silico, as well as their strengths and limitations, to extract, identify, and screen novel bioactive peptides. Once the bioactivities have been ascribed to a peptide using various in silico tools, docking is performed with the target to assess its interaction. Then, in vitro and in vivo experiments are designed to check their activity and efficacy on animal models. The discovery of novel bioactive peptides, augmented by advancements in recombinant technology and machine learning, is bound to keep pharmaceutical companies interested in peptide-based drugs. In addition, we have also discussed medicinal plants and novel approaches, such as DNA-based bioactive peptide development approaches currently being utilized in this regard. © 2024 Elsevier B.V.